Innovation-Investment Activity in Industrial Enterprises Descriptive Indicators Analysis and Impact Indicator Factors Classification - Kulbaevna, Tarakhtieva Gulmira (Journal of Business and Halal Industry, 2024)
This is it in the article industry of enterprises innovation and investment of issues In order to evaluate the harmonious aspects, the description and factors are presented, mainly the world to the experience surfaced. However, innovation and of investment one level in application The theoretical basis of the author's approach to the acquisition of characteristics for industrial enterprises given.